Education of handicapped children: problems and solutions - Prasad, Janardan; Prakash, Ravi (India, 2004)
This book is receiving attention all the world over. Educationists and social reformers have come out with techniques and principles of dealing with mentally and physically handicapped children. This book for the first times deals about both the physically
Keywords: Education- Handicapped Children